2007
DOI: 10.1007/s11096-007-9112-4
|View full text |Cite
|
Sign up to set email alerts
|

Sources of information for new drugs among physicians in Thailand

Abstract: The information sources on new drugs most frequently used by the physicians include scientific conferences, journals and medical representatives and they yearn for unbiased information regarding safety and efficacy of the promoted drugs before prescribing the new medicines. Thus, there is a window of opportunity for hospital pharmacists to serve the unmet needs of the physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…5 The younger physicians in this study revealed that, they preferred getting information from the medical representatives or at conferences to reading journals. Medical representatives were likely to be their initial sources of information about new drugs, however, they regarded this channel less reliable compared to other sources.…”
Section: Percentagementioning
confidence: 76%
See 4 more Smart Citations
“…5 The younger physicians in this study revealed that, they preferred getting information from the medical representatives or at conferences to reading journals. Medical representatives were likely to be their initial sources of information about new drugs, however, they regarded this channel less reliable compared to other sources.…”
Section: Percentagementioning
confidence: 76%
“…Studies in literature have documented mixed preference among physician and influence from the pharmaceutical industry. [1][2][3][4][5][6] The present study is the first attempt at identifying the preference for drug information sources among postgraduate medical residents at a tertiary care hospital in Navi Mumbai.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations